Pengaruh Model Problem Based Learning (PBL) Berbantuan LKPD Terhadap Hasil Belajar Siswa Kelas X Fase E di SMA N 1 IX Koto Sungai Lasi - Arbi, Joko; Roza, Helvita; Afrahamiryano, Afrahamiryano; Amri, Chairul; Wati, Darmanella Dian Eka; Dewi, Ratih Komala; Hanafi, Irwan (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the problem-based learning (PBL) model assisted by LKPD on the learning outcomes of grade X phase E students at SMA N 1 IX Koto Sungai Lasi. The type of research is a quasi-experiment. The population in this study consists of 3 classes of grade X phase E at SMA N 1 IX Koto Sungai Lasi. Sampling was conducted using Purposive Sampling, selecting classes X E1 and X E3 as the experimental and control classes. The instrument used is a final test. Data analysis technique used hypothesis testing with the Mann-Whitney test. The results of the analysis show that the final test scores obtained an average score of 84.83 for the experimental class and an average score of 71.25 for the control class. After conducting a non-parametric statistical test using SPSS, the calculated Asymp value was .006 while the table Asymp value is >0.05, which means the calculated Asymp is smaller than the table Asymp, hence H0 is rejected and H1 is accepted meaning the biology learning outcomes of students taught with the problem-based learning model assisted by LKPD are better. It can be concluded that there is an influence of the Problem Based Learning (PBL) model assisted by LKPD on the learning outcomes of class X phase E students at SMA N 1 IX Koto Sungai Lasi.